The Effects of Confiding on Shift Work Nurses’ Emotion Regulation and Self-Perceived Well-Being: An Online Randomized Controlled Trial - Cui Lu; Yawen Sun; Chunyan Wang; Tianyong Chen; Yi Tang (Behavioral Sciences)
Shift work nurses suffered great stress and emotion dysregulation during the COVID-19 pandemic. Interpersonal emotion regulation has emerged as a promising therapeutic approach, often facilitated through confiding. It has been suggested that medical staff benefit from confiding, with the act of reflecting on the social support gained from confiding being associated with higher well-being. Consequently, we hypothesized that thinking about the social support derived from confiding about work-related hassles could enhance emotion regulation and well-being in shift work nurses. This study aimed to evaluate the effects of the intervention “thinking about the social support obtained from confiding about work-related hassles” on shift work nurses’ emotion regulation and self-perceived well-being. An online randomized controlled trial was conducted with 66 shift work nurses, including 34 in the experimental group and 32 in the control group, to assess the impact of an 8-week confiding intervention focused on thinking about the social support obtained from confiding. The results indicated that the intervention significantly improved the interpersonal emotion regulation of shift work nurses in the experimental group compared to the control group. In terms of intrapersonal emotion regulation, the intervention appeared to reduce the cognitive reappraisal in the intervention group; however, there was no significant difference in cognitive reappraisal or expressive inhibition between the intervention group and control group. Furthermore, self-rated general health and sleep quality showed significant improvement in the intervention group compared to pre-test levels, but no significant differences were observed between the experimental and control groups. In conclusion, the online confiding intervention effectively enhanced interpersonal emotion regulation among shift work nurses. However, its effects on intrapersonal emotion regulation were not significant. Similarly, while participants in the intervention group reported improved self-rated general health and sleep quality, these improvements did not significantly differ from those in the control group.